Pelatihan Inovasi Produk Makanan Singkong dan Penataan Homestay - Diana Simanjuntak; Erie Sukriadi; Darmawan Sunarja (Universitas Majalengka, 2023)
Tourism villages are an alternative to increasing the welfare of the local community by participating in these activities but still maintaining the customs, uniqueness, and local wisdom of the village. One of them is the Cireundeu traditional village which has been named a tourist village in the city of Cimahi with its uniqueness, one of which is replacing eating rice with “rasi” (cassava rice). This training on product innovation and homestay arrangement aims to further improve product alternatives for selling various foods made from cassava, as well as homestays to strengthen aspects of local wisdom in the arrangement. The method used is a direct demonstration in front of the training participants. The results of this training were innovations in food products from cassava. There were two types of food, namely cassava pudding and cassava donuts. The arrangement of the homestay added the attributes of the village's local wisdom in two places, namely the homestay owned by Mrs. Neneng and Mrs. Rita. So it is hoped that this training can provide knowledge as well as skills to further improve the quality of services provided to visitors who come to the village.